Exploring The Efficacy Of Ayurveda And Panchakarma In Femoral Head Avn: A Critical Integrative Review - Haidar, Md; Ghosh, Sukumar (Journal of Neonatal Surgery, 2025)
Avascular necrosis (AVN) of the femoral head is a debilitating condition caused by compromised blood supply, leading to osteocyte death and progressive joint degeneration. Conventional treatments such as bisphosphonates, core decompression, and arthroplasty often provide limited long-term efficacy and are associated with high recurrence or complications. This necessitates the exploration of integrative approaches. Ayurveda provides a unique perspective on such degenerative bone conditions through the concepts of Dhatu Kshaya (tissue depletion), Vata Prakopa (vitiation of Vata), and Asthi-Majja Dushti (derangement of bone and marrow tissues). The present review critically explores Ayurvedic management strategies for femoral head AVN, with a focus on Panchakarma therapies (Basti, Abhyanga, Swedana, etc.) and Rasayana interventions using classical formulations and herbs like Ashwagandha, Guduchi, Shilajatu, and Guggulu. A comparative analysis of classical references, modern scientific studies, and reported clinical experiences is undertaken to formulate an integrative model for AVN management. This review highlights the potential of Ayurvedic interventions in not only halting the progression of the disease but also supporting regeneration and functional improvement. The findings suggest that Panchakarma and Rasayana, when administered appropriately, can enhance bone metabolism, improve vascular perfusion, reduce inflammation, and support overall joint health. Thus, Ayurveda may offer a safe and sustainable therapeutic approach in femoral head AVN, especially in early to moderate stages, warranting further scientific validation.